Localization of hyperpolarization-activated cyclic nucleotide-gated channels in the vertebrate retinas across species and their physiological roles - Kim, Daniel; Roh, Hyeonhee; Lee, Hyung-Min; Kim, Sang Jeong; Im, Maesoon (Frontiers in Neuroanatomy, 2024)
Transmembrane proteins known as hyperpolarization-activated cyclic nucleotide-gated (HCN) channels control the movement of Na+ and K+ ions across cellular membranes. HCN channels are known to be involved in crucial physiological functions in regulating neuronal excitability and rhythmicity, and pacemaker activity in the heart. Although HCN channels have been relatively well investigated in the brain, their distribution and function in the retina have received less attention, remaining their physiological roles to be comprehensively understood. Also, because recent studies reported HCN channels have been somewhat linked with the dysfunction of photoreceptors which are affected by retinal diseases, investigating HCN channels in the retina may offer valuable insights into disease mechanisms and potentially contribute to identifying novel therapeutic targets for retinal degenerative disorders. This paper endeavors to summarize the existing literature on the distribution and function of HCN channels reported in the vertebrate retinas of various species and discuss the potential implications for the treatment of retinal diseases. Then, we recapitulate current knowledge regarding the function and regulation of HCN channels, as well as their relevance to various neurological disorders.